Hypotensive effects of aqueous extract of Eugenia polyantha leaves are partly mediated via cholinergic receptor - Ismail, Azlini; Sulaiman, Siti Amrah; Mohamed, Mahaneem; Syed Sahil Jamalullail, Syed Mohsin (National Library of Malaysia, 2011)
Eugenia polyantha leaves, a popular fresh salad (‘ulam’) used by the Kelantanese has been claimed as a cure for hypertension. In this study, the hypotensive effects of aqueous extract of Eugenia polyantha leaves (AEEP) on the anaesthetized male normotensive Wistar-Kyoto rats were described. Increasing intravenous doses of AEEP (0.01, 0.1, 1, 10 and 100 mg/kg) significantly reduced the mean arterial blood pressure (MAP) of twelve animals by 6.06 ± 4.1 %, 8.02 ± 3.9 %, 6.35 ± 0.6 %, 9.34 ± 1.6 % and 30.19 ± 2.0 % (Wilcoxon-Signed Rank test or WSR, p<0.01) respectively. However, only reductions in MAP, by the doses of 0.1, 1, 10 and 100 mg/kg of AEEP and by the positive control (5 µg/kg acetylcholine, 37.87 ± 1.7 %) were significantly higher than the reduction of MAP by the negative control (0.9 % normal saline, 5.372 ± 0.5 %) (WSR test, p<0.05). From the dose-response curve, the ED50 value for hypotensive effects of AEEP was 35.5 mg/kg. Subsequently, a pharmacological antagonistic study was carried out either of pre-treatment with propranolol (2 mg/kg) or by pre-treatment with atropine (2 mg/kg). Pre-treatment with atropine (2 mg/kg) significantly reduced the hypotensive effect of 100 mg/kg of AEEP (WSR test, p<0.05) whilst pre-treatment with propranolol (2 mg/kg) does not significantly reduced the hypotensive effect of 100 mg/kg AEEP (WSR test, p>0.05). This attenuation suggested that the hypotensive effect of AEEP may be partly mediated by cholinergic but not by β-adrenergic receptor pathways.